Chronic low‐grade inflammation predicts greater decline in verbal fluency and word‐list learning on 10 years' follow‐up. (31st December 2021) - Kipinoinen, Teemu; Toppala, Sini; Viitanen, Matti; Rinne, Juha O.; Jula, Antti; Ekblad, Laura L.
Abstract: Background: Processes leading to the clinical presentation of Alzheimer´s disease (AD) start to develop years or even decades beforehand. Chronic low‐grade inflammation is suggested to play a role in the pathogenesis of many aging‐related chronic illnesses, including AD. The aim of this study was to evaluate whether low‐grade inflammation, commonly associated with obesity and the metabolic syndrome, is associated in cognitive decline after 10 years. We hypothesized that low‐grade inflammation at midlife, estimated by tumor necrosis factor alpha (TNF‐α), Interleukin‐6 (IL‐6) and high‐sensitivity CRP (hs‐CRP), predicts cognitive decline. Method: 915 subjects aged 45 to 74 years (median age 54, 55% women) participated a Finnish nationwide, population‐based Health 2000 Examination Survey, its supplemental cardiovascular and metabolic examinations in 2000‐2001 and the follow‐up Health 2011 Survey. Associations between baseline low‐grade chronic inflammation and cognitive performance at follow‐up in 2011 and the change in cognition from baseline to follow‐up were evaluated. TNF‐α, IL‐6 and hs‐CRP were measured in 2001. Categorical verbal fluency (VF), word‐list learning (WLL) and word‐list delayed recall (WLDR) were used as measures of cognitive performance at baseline and at follow‐up. Statistical analyses were performed with multivariable linear models adjusted for age, sex, education, APOEε4 genotype, type 2 diabetes, hypertension, hypercholesterolemia, body mass index, depressive symptoms and smoking, and for the change in cognition also baseline cognition. Result: Higher TNF‐α and IL‐6 at baseline individually predicted poorer performance in all three cognitive tests at follow‐up (VF: TNF‐α slope:‐2.29, p=0.003, IL‐6 slope:‐1.71, p<0.0001; WLL: TNF‐α slope:‐1.02, p=0.02, IL‐6 slope:‐0.80, p=0.002; WLDR: IL‐6: slope:‐0.30, p=0.02). TNF‐α and IL‐6 predicted also a greater decline in VF (TNF‐α slope:‐1.69, p=0.009, IL‐6 slope:‐1.34, P=0.0009) from baseline to follow‐up. IL‐6, but not TNF‐α predicted greater decline in WLL (IL‐6 slope:‐0.71, p=0.02) and WLDR (IL‐6: slope:‐0.30, p=0.01). Baseline hs‐CRP was not associated with cognitive performance or decline after 10 years. Conclusion: In this middle‐aged population, low grade inflammation measured with TNF‐α and IL‐6 predicts worse cognitive performance and IL‐6 predicts greater decline in cognitive function over a 10‐year follow‐up. Potentially, developing interventions that target these inflammatory processes could help reduce cognitive decline in the future.